Insect-derived polymer hydrogel based on fibroin matrix from whole silkworm larvae - Maki Yamazaki; Aoi Tojo; Shusuke Hashimoto; Masakazu Kobayashi; Kenjiro Yazawa; Kunihiro Shiomi (PLoS ONE, 2025)
Insect-derived polymers, known for their mechanical properties, biocompatibility, and sustainability, are increasingly used in pharmaceuticals, food, and tissue engineering. Bombyx mori , the silkworm, produces silk fibroin (SF) and sericin, both crucial for biomaterial development. In this study, we aimed to prepare a hydrogel derived from whole silkworm larvae powder (B100rw) without additional gelling agents and to investigate its gelation behavior. The gelation process was analyzed by examining the compressive stress, adhesiveness, and gelation time under low-temperature conditions. Structural characterization was performed using Fourier-transform infrared spectroscopy and wide-angle X-ray scattering to determine the β-sheet content and crystallinity of the hydrogel. The gelation behavior and mechanical properties of B100rw and SF hydrogels were compared. The B100rw hydrogel exhibited gelation primarily due to fibroin heavy chain (FibH), as evidenced by the failure of gelation when FibH was knocked out in the larvae. The hydrogel demonstrated significantly higher compressive stress and adhesiveness at low temperatures than SF hydrogels, with faster initial gelation. Structural analysis revealed that the B100rw hydrogel possessed a β-sheet conformation similar to SF hydrogels but with lower crystallinity. The presence of additional insect-derived polymers like sericin, chitin, and cellulose in B100rw likely contributed to these enhanced gelation properties. This study successfully developed a novel hydrogel from B100rw, demonstrating distinct gelation behavior and unique mechanical properties compared to traditional SF-based hydrogels. The findings suggest that B100rw-derived hydrogels could be used as multifunctional platforms for food and medical applications, leveraging the natural gelling properties of insect-derived polymers. Further research into optimizing the gelation process and exploring alternative insect-derived polymer hydrogels could enhance the potential of these materials for biotechnological applications.